Biodegradable, electro-active chitin nanofiber films for flexible piezoelectric transducers. (June 2018) - Kim, Kyungtae; Ha, Minjeong; Choi, Byeongwook; Joo, Se Hun; Kang, Han Sol; Park, Ju Hyun; Gu, Bongjun; Park, Chanho; Park, Cheolmin; Kim, Jongbok; Kwak, Sang Kyu; Ko, Hyunhyub; et al.
Abstract: Since the conventional fluorine-based electro-active polymers release toxic residues into the environment during their syntheses and decomposition processes, eco-friendly piezoelectric polymers are urgently demanded in the field of energy-related soft materials. Here, we derive a high-performance biodegradable chitin polymer from squid pen material and demonstrate its utility as a flexible piezoelectric material. The readily controlled ferroelectric chitin film confers excellent piezoelectricity under external mechanical pressure, resulting in comparable performance with that of conventional fluorine-based piezoelectric polymers. In particular, the sufficient piezoelectric behavior in chitin film allows us to not only realize a high-fidelity paper-type speaker and microphone that operates over a wide frequency range without significantly deteriorating the input and output sounds but also demonstrate transparent speaker consisting of AgNWs electrodes onto freestanding chitin film which also enables to resemble the original sound. Finally, the biodegradable chitin polymer can be successfully dissolved by chitinase enzyme within eight days without any toxic residues remained. Graphical abstract: We present a novel biodegradable piezoelectric material from chitin material, the second-most abundant polysaccharide biopolymer. The decent polarization arising from the chitin molecules not only facilitates the piezoelectric response upon the external pressure but also generates the harmonic frequencies of the input music source. Moreover, the environmentally friendly chitin film can be completely dissolved in a water-based solution without generating toxic products. fx1 Highlights: Ferroelectric characteristic is confirmed by polarization measurement. β-chitin film enables to demonstrate high-fidelity paper-type speaker and microphone. The biodegradable nature of chitin film can be dissolved within eight days.